Manajemen Sumber Daya Manusia dalam Pengembangan Madrasah Berbasis Digital pada Madrasah Aliyah Negeri Lhokseumawe - Ira Gusriani; Agus Salim Salabi; Yuliza Yuliza (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to analyze human resource management in the development of digital-based madrasahs at MAN Lhokseumawe and examine the obstacles faced by human resource management in the development of digital-based madrasahs at MAN Lhokseumawe. The method used in research is the case study approach or paradigm at MAN Lhokseumawe through interview, observation and documentation study techniques. The data analysis used by Mathew B. Miles' theory through the stages of data condensation, data presentation and conclusions. The subjects of the study are teachers and education personnel. The results of human resource management research in the development of digital-based madrasah are carried out by planning; identify the needs of teachers and education personnel planned in meetings attended by the head of the madrasah with the management team, implementation; training, seminars, workshops, application upgrades, and skills in the use of assets owned by schools JIBAS application and AKSIMAPEL application, evaluation; increased work motivation, supervision for teachers, reports and performance of education personnel, Wi-Fi networks, financing in the procurement of digital equipment, follow-up; deliberation and guidance in increasing work motivation, financing in the procurement of digital equipment, training plans, workshops and comparative studies according to HR needs. As for the obstacles faced in the title of human resource management in the development of digital madrasahs, namely in the form of performance motivation, adding Wi-Fi networks, financing in the procurement of digital support tools.